Mental Health Status of Senior Citizens Living in Tansen Municipality, Palpa District. - Sharma,Muna (2020)
ABSTRACT: Background The proportion of senior citizens is increasing in Nepal and they are at higher risk of developing mental health problems. The commonest mental health problems are depression and anxiety and if not diagnosed and treated early may end to suicide. Therefore, this study was conducted to find out the status and factors associated with senior citizens‟ depression and anxiety in Tansen. Methods A cross sectional study was conducted at Tansen Municipality, Palpa. From the list of senior citizens, enrolled in senior citizen allowance scheme of Nepal Government, 245 were selected randomly. Standard tools {Geriatric Depression Scale (short version) and Geriatric Anxiety Scale-10} were used to collect data about mental health problems of senior citizens. Face to face interview was done by visiting the participants in their household to collect data from Feb, 27, 2020 to March, 18, 2020. The data was entered in Epi Data 3.1 and transferred to SPSS version 16 program for analysis. Descriptive statistics, Spearman‟s Rho, chi square and odds ratio calculation was done. Results Out of 245 senior citizens, 52.2% were female and 47.8% were male. The mean age of the participants was 78.33 with ± 6.30 SD. Among them, 35.9% were widow and widower, 4.9% had no companion to live life, 95.5% were physically independent, and 68.2% were living with physical comorbid condition. It was found that 67.3% respondents had no depression, 30.6% had suggestive of depression, and 2% respondents‟ symptoms were indicative of depression. Similarly, 64.5% participants had minimal symptoms of anxiety, whereas 11.8% and 8.2% had moderate and severe symptoms of anxiety respectively. The anxiety and depression were corelated (rs = 0.615, p = 0.000). The associated factors of depression were marital status (p=0.001), companion of living (p=0.000), sex (p=0.012, OR= 2.010), education status (p=0.004), physical dependency (p=0.000), presence of physical health problem (p=0.000, OR = 2.408), and having medication (p = 0.015 OR = 2.127). Factors associated with anxiety were marital status (p = .001, OR = 3.002) living companion (p = 0.004), education status (p = 0.000, OR = 3.673), ethnicity (p=0.020), and physical dependency (p = 0.005, OR = 6.698) of the participants. Conclusion The senior citizens have symptoms of depression and anxiety. Female sex, having physical health problem and regular medication are likely to increase depression. Similarly, anxiety tends to occur among senior citizens with widow/widower and illiteracy. There is a need to recognize the mental health problem of elderly in community setting. Keywords Anxiety, Depression, Senior citizens, Geriatrics, Elderly people, Tansen, Nepal